Religion, race, and Reconstruction : the public school in the politics of the 1870s - McAfee, Ward (SUNY series, religion and American public life., 1998)
"Religion, Race, and Reconstruction simultaneously resurrects a lost dimension of a most important segment of American history and illuminates America's present and future by showing the role religious issues played in Reconstruction during the 1870s."--Jacket